DNA virus oncoprotein HPV18 E7 selectively antagonizes cGAS‐STING‐triggered innate immune activation. Issue 1 (21st November 2022) - Lou, Meng; Huang, Dingbo; Zhou, Zhenbang; Shi, Xinyu; Wu, Miaowei; Rui, Yajuan; Su, Jiaming; Zheng, Wenwen; Yu, Xiao‐Fang
Abstract: Cellular infections by DNA viruses trigger innate immune responses mediated by DNA sensors. The cyclic GMP–AMP synthase (cGAS)‐stimulator of interferon gene (STING) signaling pathway has been identified as a DNA‐sensing pathway that activates interferons in response to viral infection and, thus, mediates host defense against viruses. Previous studies have identified oncogenes E7 and E1A of the DNA tumor viruses, human papillomavirus 18 (HPV18) and adenovirus, respectively, as inhibitors of the cGAS‐STING pathway. However, the function of STING in infected cells and the mechanism by which HPV18 E7 antagonizes STING‐induced Interferon beta production remain unknown. We report that HPV18 E7 selectively antagonizes STING‐triggered nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NF‐κB) activation but not IRF3 activation. HPV18 E7 binds to STING in a region critical for NF‐κB activation and blocks the nuclear accumulation of p65. Moreover, E7 inhibition of STING‐triggered NF‐κB activation is related to HPV pathogenicity but not E7–Rb binding. HPV18 E7, severe acute respiratory syndrome coronavirus‐2 open reading frame 3a, human immunodeficiency virus‐2 viral protein X, and Kaposi's sarcoma‐associated herpesvirus KSHV viral interferon regulatory factor 1 selectively inhibited STING‐triggered NF‐κB or IRF3 activation, suggesting a convergent evolution among these viruses toward antagonizing host innate immunity. Collectively, selective suppression of the cGAS‐STING pathway by viral proteins is likely to be a key pathogenic determinant, making it a promising target for treating oncogenic virus‐induced tumor diseases.